Caracterização geomorfológica e modelagem de dados espaciais na plataforma continental rasa do RN nos limites da folha Touros - Araújo Filho, Lino Pedro de (2011)
This work focuses the geomorphological characterization and spatial data modeling in the shallow continental shelf within the Folha Touros limits (SB-25-CV-II), based on bathymetric data analysis and remote sensing products interpretation. The Rio Grande do Norte state is located in northeastern Brazil and the work area is located at the transition region between the eastern and northern portions of their coast. The bathymetric surveys were conduced between march and may 2009, using a 10 meters long vessel and 0.70 meters draught, equipped with global positioning system and echo sounder (dual beam, 200KHz , 14°). The fieldwork resulted in 44 bathymetric profiles espaced 1.5 km and 30 km average length. The bathymetric data amount were 111,200 points and were navigated 1395.7 km within na area about 1,850 km2. The bathymetric data were corrected for the tide level, vessel draught and were subsequently entered into a geographic information system for further processing. Analysis of remote sensing products was carried out using Landsat 7/ETM + band 1, from november 1999. The image was used for visualization and mapping submerged features. The results showed the presence of geomorphological features within the study area. Were observed, from the analysis of local bathymetry and satellite image, seven types of geomorphological features. The channels, with two longitudinals channels (e. g. San Roque and Cioba channels) and other perpendicular to the coast (e. g. Touros, Pititinga and Barretas). Coastal reef formations (Maracajaú, Rio do Fogo and Cioba). Longitudinal waves, described in the literature as longitudinal dunes. The occurrence of a transverse dune field. Another feature observed was the oceanic reefs, an rock alignment parallel to the coast. Were identified four riscas , from north to south: risca do Liso, Gameleira, Zumbi, Pititinga (the latter being described for the first time). Finally, an oceanic terrace was observed in the deepest area of study. Image interpretation corroborated with the in situ results, enabling visualization and description for all features in the region. The results were analysed in an integrating method (using the diferent methodologies applied in this work) and it was essential to describe all features in the area. This method allowed us to evaluate which methods generated better results to describe certain features. From these results was possible to prove the existence of submerged features in the eastern shallow continental shelf of Rio Grande do Norte. In this way, the conclusions was (1) this study contributed to the provision of new information about the area in question, particularly with regard to data collection in situ depths, (2) the method of data collection and interpretation proves to be effective because, through this, it was possible to visualize and interpret the features present in the study area and (3) the interpretation and discussion of results in an integrated method, using different methodologies, can provide better results